2020
DOI: 10.1111/1462-2920.15191
|View full text |Cite
|
Sign up to set email alerts
|

A non‐flagellated, predatory soil bacterium reprograms a chemosensory system to control antifungal antibiotic production via cyclic di‐GMP signalling

Abstract: Summary Lysobacter enzymogenes is a non‐flagellated, soil proteobacterium that secretes a diffusible antibiotic known as heat‐stable antifungal factor (HSAF) to kill nearby fungi for food. The genome of the model strain OH11 encodes a homologous Wsp system, which is generally deployed by flagellated bacteria to achieve flagella‐dependent outputs via a c‐di‐GMP‐FleQ complex, in which c‐di‐GMP is a ubiquitous dinucleotide second messenger and FleQ is a transcription factor (TF). Here, we show that the Wsp system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…LchD is a new addition to the network of c‐di‐GMP synthesizing and degrading enzymes involved in HSAF biosynthesis. This list includes the DGC WspR and two PDEs, LchP and RpfG (Xu et al., 2018, 2021). We recently showed that WspR directly interacts with the c‐di‐GMP‐binding coactivator CdgL (YajQ), which together with the transcription factor LysR activates the HSAF biosynthesis operon (Han et al., 2020; Xu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…LchD is a new addition to the network of c‐di‐GMP synthesizing and degrading enzymes involved in HSAF biosynthesis. This list includes the DGC WspR and two PDEs, LchP and RpfG (Xu et al., 2018, 2021). We recently showed that WspR directly interacts with the c‐di‐GMP‐binding coactivator CdgL (YajQ), which together with the transcription factor LysR activates the HSAF biosynthesis operon (Han et al., 2020; Xu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, incomplete (c.70%) restoration of the ΔpilR phenotype by the ΔlchD deletion points to the existence of yet another pathway through with PilR affects HSAF production (Figure 4). This list includes the DGC WspR and two PDEs, LchP and RpfG (Xu et al, 2018(Xu et al, , 2021. We recently showed that WspR directly interacts with the c-di-GMP-binding coactivator CdgL (YajQ), which together with the transcription factor LysR activates the HSAF biosynthesis operon (Han et al, 2020;Xu et al, 2021).…”
Section: F I G U R Ementioning
confidence: 99%
See 3 more Smart Citations